Household Air Pollution and Blood Pressure, Vascular Damage, and Subclinical Indicators of Cardiovascular Disease in Older Chinese Adults. (10th September 2021) - Kanagasabai, Thirumagal; Xie, Wuxiang; Yan, Li; Zhao, Liancheng; Carter, Ellison; Guo, Dongshuang; Daskalopoulou, Stella S; Chan, Queenie; Elliott, Paul; Ezzati, Majid; Yang, Xudong; Xie, Gaoqiang; et al.
Abstract: Background: Limited data suggest that household air pollution from cooking and heating with solid fuel (i.e., coal and biomass) stoves may contribute to the development of hypertension and vascular damage. Methods: Using mixed-effects regression models, we investigated the associations of household air pollution with blood pressure (BP) and vascular function in 753 adults (ages 40–79 years) from 3 diverse provinces in China. We conducted repeated measures of participants' household fuel use, personal exposure to fine particulate air pollution (PM2.5 ), BP, brachial–femoral pulse wave velocity (bfPWV), and augmentation index. Ultrasound images of the carotid arteries were obtained to assess intima–media thickness (CIMT) and plaques. Covariate information on sociodemographics, health behaviors, 24-h urinary sodium, and blood lipids was also obtained. Results: Average estimated yearly personal exposure to PM2.5 was 97.5 µg/m 3 (SD: 79.2; range: 3.5–1241), and 65% of participants cooked with solid fuel. In multivariable models, current solid fuel use was associated with higher systolic (2.4 mm Hg, 95% CI: −0.4, 4.9) and diastolic BP (1.4 mm Hg, 95% CI: −0.1, 3.0) and greater total area of plaques (1.7 mm 2, 95% CI: −6.5, 9.8) compared with exclusive use of electricity or gas stoves. A 1 − ln(µg/m 3 ) increase in PM2.5 exposure was associated with higher systolic (1.5 mm Hg, 95% CI: 0.2, 2.7) and diastolic BP (1.0 mm Hg, 95% CI: 0.4, 1.7) and with greater CIMT (0.02 mm, 95% CI: 0.00, 0.04) and total area of plaques (4.7 mm 2, 95% CI: −2.0, 11.5). We did not find associations with arterial stiffness, except for a lower bfPWV (−1.5 m/s, 95% CI: −3.0, −0.0) among users of solid fuel heaters. Conclusions: These findings add to limited evidence that household air pollution is associated with higher BP and with greater CIMT and total plaque area. Graphical Abstract: